Three technical challenges of scaling from social virtual reality to metaverse(s): interoperability, awareness and accessibility - Steed, Anthony (Frontiers in Virtual Reality, 2024)
The development of metaverse systems is marked by uncertainty regarding their technical architecture and the scope of their capabilities. Current social virtual reality (SVR) systems offer glimpses of future metaverse environments but remain fragmented, with limited interoperability, poor discoverability, and challenges in preserving assets and social capital across different platforms. Drawing parallels with the evolution of the Internet and World Wide Web, the essay argues that while certain metaverse standards may emerge naturally, fundamental challenges persist, particularly concerning client software. The essay highlights three overlooked yet critical issues for user experience: interoperability, scalable awareness, and accessibility. These challenges, often underemphasized in current standards discussions, are crucial for the practical development of user-friendly metaverse systems.